Challenges and strategies to face agrometeorological risks and uncertainties – Regional Perspective in South America - Alarcón Velazco, Constantino (2007)
South America is one of the regions in the world, most exposed to a wide range of hydro-meteorological hazards, according to the EM-DAT, an international database on disasters, that the Office of US Foreign Disaster Assistance (OFDA) is in charge of. The Center for Research on the Epidemiology of Disasters (CRED) estimates that between 1980 and 2005, almost 80% of the natural disasters, 30% of the loss of human life and 75% of economic loss that took place in the Region were caused by hydro-meteorological conditions and hazards. In south american where agriculture, fishery and forestry contribute 12% of the Gross Domestic Product (GDP), the success of these activities depends basically on a favourable climate A good rainy period, together with adequate temperature conditions and the absence of extreme weather, guarantee the sucess of agriculture conditions and the absence of extreme weather, guarantee the success of agricultural productions. Despite its importance, agriculture is the sector most vulnerable to natural disasters.